Thirty-seven Years of Silvicultural Research in the Madras State 1919 to 1956 - a Historical Outline - Venkataramany, P. (Indian Forester, 1956)
The beginnings of Silvicultural Research in Madras State in 1919 are described and the progress achieved during the last 37 years is referred to. Mention is made of the work of the previous Silviculturists. Details are furnished regarding Ledger Files, Experimental Plot Files, Experimental Garden Files, and Sample Plots, during the period. The subjects taken up for research in the early years are referred to and it is shown how due to patient research on the Artificial Regeneration of Teak, perfection was attained about the thirties. The experiments on the Natural Regeneration by Coppice and Artificial Regeneration of Fuel Forests are given. The experiments on Eucalyptus globulus (Blue gum), Acacia mollissima (Wattle), and Casuarina equisetifolia are referred to in brief. Research on the Afforestation of Dry Fuel Forests was comparatively neglected in the past. This deficiency is sought to be made good by expansion of research and opening of several new centres in the East Coast and in the central Districts during the year 1954-55. The progress of research on the eradication of Lantana camara is referred to. The history of research on the Spike Disease of Sandal is then described briefly. An instance is quoted to show that in research, conclusions should not be drawn hastily. The part played by the F.R.I., Dehra Dun in the organization of research in the Madras State is described.